Reducing bias in shopping mall-intercept surveys: The time-based systematic sampling method - Johan de W. Bruwer; Norbert E. Haydam; Binshan Lin (South African Journal of Business Management, 1996)
Marketing practitioners nowadays often have to base important management decisions on information obtained in research surveys conducted in shopping malls. The shopping mall-intercept survey is a very popular method used by research agencies to gather information of almost all kinds. While the advantages of shopping mall-intercept interviewing are considerable, their adoption without recognition of their shortcomings is not prudent. Selection error, resulting in time sampling bias, occurs in shopping mall-intercept surveys as a result of significant differences between the characteristics of persons visiting a shopping mall at different time segments during a month period. In this empirical study, the authors explain the problem of time-based selection error in mall-intercept data, the failure of common research practices to correct it, and develop a specific time-bias reduction technique.
Keywords: 650